Thinking skills in Primary Education: An Analysis of CLIL Textbooks in Spain - Romeu Peyró, María Candelaria; Cerezo Herrero, Enrique; Llamas Pérez, Encarna (Porta Linguarum An International Journal of Foreign Language Teaching and Learning, 2020)
In this work an analysis of CLIL textbooks based on Bloom’s taxonomy and the subsequent revision made by Anderson and Krathwohl will be conducted. The objective is to ascertain whether teachers have at their disposal a bibliographical support consistent with the didactic tenets that the CLIL methodology promotes. The bidimensional table proposed by these authors has been utilized as a tool of analysis, taking both the cognitive and knowledge dimensions into account. Within the latter, the study focuses on the metacognitive knowledge level. Six Natural Science textbooks for sixth year of Primary Education, designed by different publishers and currently in use, have been analyzed. These textbooks have been designed according to the CLIL approach. We purport to verify whether these materials develop High Order Thinking Skills (HOTS), which are necessary for the proper development of this approach. It can be concluded that 66% of the analyzed materials do not promote the necessary HOTS for the proper implementation of the CLIL approach. Therefore, a change in the elaboration of textbooks is deemed necessary.